2016
DOI: 10.1039/c5ra24654g
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimizing the performance of PVC/PVB ultrafiltration membranes using supervised learning approaches

Abstract: 17Mathematical models plays an important role in performance prediction and 18 optimization of ultrafiltration (UF) membranes fabricated via dry/wet phase inversion 19 in an efficient and economical manner. In this study, a systematic approach, namely, a 20 supervised, learning-based experimental data analytics framework, is developed to 21 model and optimize the flux and rejection rate of Poly (vinyl chloride) (PVC) and 22Polyvinyl butyral (PVB) blend UF membranes. Four supervised learning (SL) 23 approaches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Moreover, PVC can be dissolved in various industrial solvents 22 . Hence, PVC can be applied for the fabrication of membranes via the nonsolvent-induce phase separation (NIPS) process 20 , 22 24 . However, due to its inherent hydrophobicity, hydrophilic modification is necessary for fabricating PVC membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PVC can be dissolved in various industrial solvents 22 . Hence, PVC can be applied for the fabrication of membranes via the nonsolvent-induce phase separation (NIPS) process 20 , 22 24 . However, due to its inherent hydrophobicity, hydrophilic modification is necessary for fabricating PVC membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Chi et al. evaluated the use of four different supervised learning approaches for the modeling of poly(vinyl chloride)/polyvinyl butyral ultrafiltration membranes [ 13 ]. They concluded that the neural network model is preferable which was further confirmed with experimental data.…”
Section: Introductionmentioning
confidence: 99%